(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
To reduce the negative impact of industry and transport as much as possible, to achieve implementation of large-scale activities in enterprises and organizations and, as a result, to improve the level of atmospheric air quality. 10% reduction of pollutant emissions into the atmosphere (including 7% from transport and 3% from industry); 80 percent of vehicles use gas fuel and to ensure transfer to work one other alternative energy